Evaluating sectoral effects of agricultural nitrogen pollution reduction policy in Croatia within a CGE framework - Ozana Nadoveza Jelić; Jurica Šimurina (Agricultural and Food Economics, 2020)
Environmental policies are becoming an important part of agricultural policy portfolio in the EU, which is binding on Croatia. This paper seeks to evaluate potential sectoral effects of several nitrogen pollution reduction policy measures within CGE model for Croatia. Finding appropriate agri-environmental policy design represents a typical optimization problem. Thus, the paper attempts to find potential agri-environmental measures which comply with supranational directives without jeopardizing other economic policy goals. Results show that polluter-pays principlebased measures, if not accompanied by the provider-gets principle measures, could have relatively large negative economy-wide effects in Croatia. However, these effects can be reduced by the appropriate policy mix.
Keywords: 330; Agriculture; Agri-environmental policy; Small open economy; Croatia; Nitrogen pollution; Sectoral effects